2018
DOI: 10.1590/s1677-5538.ibju.2017.0071
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer recurrence in vas deferens – fusion image guide as an important tool in dignosis

Abstract: The biochemical recurrence after local treatment for prostate cancer is an often challenging condition of clinical management. The aim of this report is to demonstrate the importance of the association of various imaging methods in the identification and subsequent accurate percutaneous biopsy in patients with recurrence of prostate cancer, especially in unusual sites.An 86 years old male with biochemical recurrence, during radiological investigation a PET-MRI was noted the presence of an asymmetry of the vas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are only few prostate cancer cases with vas deferens invasion and/or tumor deposit in the inguinal canal in current literature; some of them were defined by PET/CT with PSMA expression. [3][4][5][6][7][8] Inguinal canal metastasis probably spreads via the lymphatic route, classified as M1a, indicating a poor prognosis. 3 Metastasis to vas deferens may occur directly over the seminal vesicle, via the ejaculatory duct or lymphatic/hematogenous route.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There are only few prostate cancer cases with vas deferens invasion and/or tumor deposit in the inguinal canal in current literature; some of them were defined by PET/CT with PSMA expression. [3][4][5][6][7][8] Inguinal canal metastasis probably spreads via the lymphatic route, classified as M1a, indicating a poor prognosis. 3 Metastasis to vas deferens may occur directly over the seminal vesicle, via the ejaculatory duct or lymphatic/hematogenous route.…”
Section: Figurementioning
confidence: 99%
“…Vas deferens and inguinal canal metastases of prostate cancer are rare conditions, which are overlooked by radiologists, pathologists, and clinicians. There are only few prostate cancer cases with vas deferens invasion and/or tumor deposit in the inguinal canal in current literature; some of them were defined by PET/CT with PSMA expression 3–8 . Inguinal canal metastasis probably spreads via the lymphatic route, classified as M1a, indicating a poor prognosis 3 .…”
mentioning
confidence: 99%
“…In the literature there are few cases of VD recurrence after RP, and no one reported treatment details. Valle et al [ 8 ] and Priftakis et al [ 9 ] reported a total of three VD recurrence case, detected by PET-MRI or PSMA-PET/CT. During RP, the VD are dissected and transposed caudally to their distal portion or to SV apex.…”
Section: Discussionmentioning
confidence: 99%
“…Novel technologies are emerging to increase the detection of PCa, such as MRI-TRUS fusion targeted biopsy or the prostate-specific membrane antigen (PSMA) with positron emission tomography (PET)-MRI. This method provides a more specific and accurate biopsy (17)(18)(19); however, it is still not feasible for all hospitals. A cost-benefit analysis to advocate for these technologies in all patients may not support such an action (20).…”
Section: Discussionmentioning
confidence: 99%